PERTUMBUHAN DAN HASIL DUA VARIETAS JAGUNG KETAN DENGAN JUMLAH BENIH PER LUBANG TANAM - Fatmawati, Fatmawati; R., Asmuliani; Arisanto, Afif (PLANTKLOPEDIA: Jurnal Sains dan Teknologi Pertanian, 2024)
This research aims to determine the growth and yield two varieties of waxy maize with number of seeds per planting hole. This research took place from December 2023 to Mei 2024 at Palopo Village, Marisa District, Pohuwato Regency, Gorontalo Province. This research used randomized block design consisting of one seed of kumala F1 variety waxy maize per planting hole (VB11) ; two seed of kumala F1 variety waxy maize per planting hole (VB12) ; one seed of rasanya F1 variety waxy maize per planting hole (VB21) ; and two seed of rasanya F1 variety waxy maize per planting hole (VB22). The treatment was repeated four time. Based on the results of the research, it was obtained that VB11 gave the best results in the observation plant height, number of leaves, and cob diameter without cornhusk. VB12 gave the best results on cob weight per plot and cob weight without cornhusk per sample. VB21 gave the best results on cob length with and without cornhusk, and cob diameter with cornhusk. VB22 gave the best results on number of cubs per plot and cob weight with cornhusk per sample.